A Proposed Partnership Scheme of Bangkok Mass Transit System (BTS) and MICE Corporations: Passenger Satisfaction and Tourism Transport Policy Approach - Dechen, Pem; Sanyost, Sittichai; Syah, Ahmad Mujafar (E-Journal of Tourism, 2021)
This research examined and proposed a partnership scheme between Bangkok Mass Transit System (BTS) and MICE corporations (MICE: meetings, incentives, conventions & exhibitions) where one representative from BTS and six respondents from six different MICE corporations volunteered in the study. The research was conducted by two different sequences and undertaken by a mixed methodology. Out of 400 ridership satisfaction questionnaires, 300 were validated to have ridership experiences to MICE venues with BTS. Post-passenger satisfaction study, the results were used to inform BTS and MICE corporations to navigate in-depth interviews. SPSS runs to quantify travel frequencies, demographic profiles, and passenger satisfaction while thematic analysis framed the interview results. The finding underscored the two major significances as they correspond to the objective of the study: (1) The overarching governance proposal of BTS’s short-term partnership scenario with MICE corporations - where an informed policy benchmark from “England Strategic Action Plan for Tourism 2010-2020” robustly examined; (2) the novelty over the deficient study of integrated transport-MICE strategic planning within the Southeast Asian region.